A novel approach for lactate threshold assessment based on rating of perceived exertion - Fabre, N.; Mourot, L.; Zerbini, L.; Pellegrini, B.; Bortolan, L.; Schena, F. (International Journal of Sports Physiology and Performance, 2013)
This study tested the hypothesis that the DMAX (for maximal distance) method could be applied to ratings of perceived exertion (RPE), to propose a novel method for individual detection of the lactate threshold (LT) using RPE alone during an incremental test to exhaustion. Twenty-one participants performed an incremental test on a cycle ergometer. At the end of each stage, lactate concentration was measured and the participants estimated RPE using the Borg CR100 scale. The intensity corresponding to the fixed lactate values of 2 or 4 mmol/L (2mM and 4mM), the ventilatory threshold (VT), the respiratory-compensation point (RCP), and the instant of equality of pulmonary gas exchange (RER=1.00) were determined. Lactate (DMAX La) and RPE (DMAX RPE) thresholds were determined using the DMAX method. Oxygen uptake (VO2), heart rate, and power output measured at DMAX RPE and at DMAX La were not statistically different. Bland-Altman plots showed small bias and good agreements when DMAX RPE was compared with the DMAX La and RER=1.00 methods (bias = -0.05% and -2% of VO2max, respectively). Conversely, VO2 from the DMAX RPE method was lower than VO2 at 4 mM and at RCP and was higher than VO2 at 2 mM and at VT. VO2 at DMAX RPE was strongly correlated with VO2 at DMAX La (r = .97), at RER=1.00 (r = .97), at 2 mM (r = .85), at 4 mM (r = .93), at VT (r = .95), and at RCP (r = .95). The combination of the DMAX method with the RPE responses permitted precise and individualized estimates of LT using the DMAX method